Consumo de Cannabis sativa L. “marihuana” determinado en el Laboratorio de Química y Toxicología del Complejo Policial Cap. P.N.P. Alcides Vigo Hurtado, junio-agosto 2016 - Orrillo Banda, Gennesis Judith (2017)
The present report was directed to determine the Consumption of Cannabis sativa L. "marijuana" in the Laboratory of Chemistry and Toxicology of the Police Complex Cap. P.N.P. Alcides Vigo Hurtado, June-August 2016. Tetrahydrocannabinol (THC), the main metabolite of Cannabis sativa L. "marijuana" in urine samples, was identified qualitatively by thin layer chromatography (TLC). It was found that 22% A positive result for the consumption of Cannabis sativa L. "marijuana", of them, the 31% of people with greater consumption was the district of Trujillo, 67% with ages between 18 and 30 years had a positive result for Cannabis sativa L. "marihuana", 92% of males had a positive result for Cannabis sativa L. "marihuana" and 42% had a higher consumption of Cannabis sativa L. "marihuana" in the month of June. As a result, between June and August 2016, out of 588 urine samples, 129 people consumed Cannabis sativa L. "marihuana", equivalent to 22%.